Rheological optimization of hybrid alginate-xanthan gum hydrogels for enhanced 3D bioprinting fidelity - Torres-Ayala, Lizardo K. (2025)
This study presents a systematic and reproducible methodology for the development and evaluation of hybrid hydrogels tailored for extrusion-based 3D bioprinting. To demonstrate the applicability of this approach, alginate and xanthan gum were selected as model materials, two of the most widely reported polymers in the biofabrication literature. Rather than relying on empirical trial and error, the methodology integrates material screening, rheological and chemorheological analyses, predictive modeling, and experimental validation to address key challenges in reproducibility, print fdelity, and structural stability. The AL4XA4 formulation emerged as a robust candidate, exhibiting shear-thinning behavior, rapid thixotropic recovery, and adequate mechanical strength to maintain flament integrity during extrusion. Powerlaw-based modeling enabled the rational adjustment of extrusion pressures and nozzle confgurations, leading to consistent deposition with minimal defects. Although no living cells or biological additives were used, bioprinting protocols were applied to assess printability and structural performance. The material formed self-supporting flaments with unsupported spans up to 6 mm. Chemorheological testing confrmed the reinforcing efect of ionic cross-linking (1.5-3% CaCl2) in enhancing construct stability. This framework ofers a transferable strategy for standardized bioink development and structural benchmarking, paving the way for reproducible biofabrication in tissue engineering and related biomedical applications.